The Effect of Brand Image, Brand Trust and Customer Experience on Brand Loyalty - Afiftama, Ilham; Nasir, Moechammad (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The purpose of this study was to analyze the effect of brand image, brand trust, customer experience, on brand loyalty in Baberking haircut services. This research method is quantitative. This study uses primary data, namely data obtained directly from respondents through filling out questionnaires. The sampling technique in this study was non probability sampling. The population in this study were all people who used haircuts at Baberking haircut services in Solo Raya. The sample in this study were respondents who had used haircut services at Baberking Solo Raya. The number of samples in this study were 200 respondents. Data analysis in this study is quantitative analysis using Partial Least Square (PLS) analysis. The software used in this research is Smart PLS version 3.0. The results of this study are Based on the results of the analysis and discussion that has been carried out in this study, it is found that brand image has a significant effect on brand loyalty in Barberking Solo Raya haircut services. Brand trust has a significant effect on brand loyalty in Barberking Solo Raya haircut services. Customer experience has a significant effect on brand loyalty at Barberking Solo Raya haircut services.